2022
DOI: 10.1080/13880209.2022.2157020
|View full text |Cite|
|
Sign up to set email alerts
|

Zhizhu decoction alleviates slow transit constipation by regulating aryl hydrocarbon receptor through gut microbiota

Abstract: Context Slow transit constipation (STC), the most common type of constipation, seriously affects the life of patients. Zhizhu decoction (ZZD), a traditional Chinese medicine compound, has is effective against functional constipation, but the mechanism is still unclear. Objective This research explores the mechanism of ZZD on STC from the perspective of metabolomics and gut microbiota. Materials and methods Fifty-four C57BL/6 mice were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…The pathogenesis of STC is intricate, with intestinal motility deficiency identified as a key pathological mechanism. Intestinal motility includes various physiological aspects, including contractile movement of the intestinal muscles, sensitivity of the intestinal wall, biomechanical function of the intestinal tract, and colon injury [22]. Our findings suggest a potential role for SH in mitigating constipation-induced colonic injury.…”
Section: Discussionmentioning
confidence: 71%
“…The pathogenesis of STC is intricate, with intestinal motility deficiency identified as a key pathological mechanism. Intestinal motility includes various physiological aspects, including contractile movement of the intestinal muscles, sensitivity of the intestinal wall, biomechanical function of the intestinal tract, and colon injury [22]. Our findings suggest a potential role for SH in mitigating constipation-induced colonic injury.…”
Section: Discussionmentioning
confidence: 71%
“…STC is a disease characterized by delayed colonic transport, 24-hour fecal volume, and fecal water content, and ITR can be used as a representative diagnostic indicator (10). This study found that after the intervention, the fecal water content, intestinal transport function, and pathological damage to the colon mucosa of STC rats were restored, with the high-dose group having the most significant improvement effect.…”
Section: Discussionmentioning
confidence: 87%
“…A Zhizhu decoction, consisting of Citrus aurantium (Zhi-Shi in Chinese) and Rhizoma Atractylodis Macrocephalae (Bai-Zhu in Chinese), is widely used in the treatment of functional gastrointestinal diseases caused by a spleen deficiency and Qi stagnation syndrome. The Zhizhu decoction has been reported to have beneficial laxative action on constipation in mouse models, which may be attributed to its ability to alter the composition of intestinal flora and activate the aryl hydrocarbon receptor (AHR) signaling pathway (76). In addition, the Zhizhu decoction increases the expression of Ach, SP, and 5-HT in the colon while decreasing the expression of VIP.…”
Section: Traditional Herbal Formulationsmentioning
confidence: 99%